Brain behavior during reasoning and problem solving task: An EEG study - Amin, H.U. (IEEE Computer Society, 2014)
The capacity of relational reasoning is to find relationships, comprehend implications, analyze novel problems and draw conclusions. This study has investigated brain behavior and dynamic neural activity during Raven's Advance Progressive Matrices (RAPM), which requires strong cognitive reasoning to select a solution, by using an electroencephalogram (EEG). The EEGs were recorded all over the scalps of eight healthy volunteers using the 128-channel Hydro-Cel Geodesic (EGI Inc.) system. Brain activation was dominant during the reasoning and problem solving process in the pre-frontal lobe and parietal lobe as compared to the baseline conditions in all of the subjects, consistently. The theta band (3.5-7.5Hz) was significantly (p<0.025) higher during the reasoning process at the frontal lobe as compared to eye-closed and eye-open conditions. Results showed high frontal theta activity in problem solving, which requires substantial reasoning and thinking skills. Â© 2014 IEEE.